Patients and treatments in a neuropalliative outpatient clinic: an analysis of clinical routine data from five years of care - Grimm, Teresa; Otto-Sobotka, Fabian; Steinker, Dorothee; Summ, Oliver; Timmer, Antje; Groß, Martin (Frontiers in Neurology, 2025)
IntroductionThe increasing prevalence of life-threatening neurological diseases raises the need for neuropalliative care. Setting up neurological palliative outpatient clinics is one way of addressing this need. This study aims to describe the patient clientele of a neurological palliative outpatient clinic and the spectrum of necessary treatments and interventions.MethodsIn this longitudinal analysis, clinical routine data from a single centre were collected retrospectively from adult patients. The patient characteristics related to disease and treatment were evaluated descriptively. Factors influencing the need for ventilation were modelled in a logistic regression. The required treatment effort was modelled with a zero-inflated Beta regression. Results were reported as odds ratios with 95% confidence intervals (CIs).ResultsTwo hundred and thirty-two patients were included in the study. Ninety-one patients were women, 141 were men, and the mean age was 55.42 years. Neuropalliative patients represented diagnoses such as amyotrophic lateral sclerosis (ALS) (n = 81), ischemic stroke (n = 15), intracerebral haemorrhage (n = 15), Duchenne muscular dystrophy (n = 12), or craniocerebral trauma (n = 10). Palliative care counselling was the most common intervention for patients (n = 203), their close relatives (n = 177), and their nursing services (n = 75). Respiratory therapy (n = 188), speech and language therapy (n = 145), and physiotherapy (n = 143) were also frequently applied interventions. Sixty patients received botulinum toxin A treatment for hypersalivation, and 32 for spasticity. The odds of needing invasive ventilation increased by 3.7 (CI 1.7–7.8), and the need for mechanical insufflation-exsufflation increased by 2.2 (CI 1.1–4.3) in patients previously discharged from early neurological-neurosurgical rehabilitation. Prior intensive care treatment increased the odds of invasive ventilation by 5.1 (CI 2.2–11.5) and the use of mechanical insufflation-exsufflation by 2.3 (CI 1.1–4.8).ConclusionNeuropalliative outpatient clinics demand a wide range of diagnostic measures and interventions as well as a multidisciplinary approach. Further research is necessary to investigate the relation between diagnosis and treatment needs.Clinical trial registrationhttps://drks.de/search/en/trial/DRKS00030778, identifier DRKS00030778.